Penundukan Diri Suatu Negara Terhadap Keputusan Penunjukan Uskup Oleh Takhta Suci, Pespektif Hukum Internasional - Yustinus Stevanus Yanubi; Josina Augustina Yvonne Wattimena; Johanis Steny Franco Peilouw (PAMALI: Pattimura Magister Law Review, 2022)
Introduction: The existence of the Holy See is recognized in the international community, especially in matters of religious spirituality to appoint bishops as part of its rights as subjects of international law.Purposes of the Research:  This study aims to find out how the existence of the Holy See as a subject of international law in confession by international community, and how the submission of a state in international law to the decision to appoint bishops by the Hole See.Methods of the Research: This study uses a normative legal research method, which aims to find out how the existence of the Holy See as a subject of international law in confession by international community, and how the submission of a state in international law to the decision to appoint bishops by the Hole See.Results / Findings / Novelty of the Research: The existence of the Holy See as a subject of international law is recognized through the recognition of states of the decision to appoint bishops by the Pope. The decision to appoint bishops by the Pope is basically capable of making states submit to themselves. This is reflected in various forms of recognition by states such as positive legal recognition, political recognition, and tacit recognition. In the context of the case with the Chinese government, it can be seen that China has made tacit recognition of the Pope’s authority in appointing bishops. So, that can be firmly said that the recognition is a respect for the rights of the Holy See in accordance with international law.